Analysis of the scope of the structural review of the POT of Bogotá, in terms of equipment proposed within the framework of regional integration, with the western sheet (2019)
The planning of the territory, as the norm refers to, especially Decree 879 of 1998 in its article 2, “aims to give economic and social planning its territorial dimension, rationalize intervention on the territory and promote its development and sustainable use ". This is how territorial planning acts in all aspects of society, because “The life of human beings is linked to the territory” (Externado University, 2019), which denotes a great responsibility of the human being, since it is who it must plan the adequate and sustainable use of the territories currently disintegrated and faced by the territory's own difficulties resulting from geographical isolation and lack of cohesion and regional perspective. In virtue of the foregoing, territorialization involves the generation of land-use planning plans, their articulation between cities and the prevalence of common interest for the consolidation of other public policies that seek to materialize the essential purposes of the State. And to achieve this, you must have the commitment and will of the public actors, authors of the technical exercise of planning.